Testing the usefulness of optical data for zooplankton long‐term monitoring: Taxonomic composition, abundance, biomass, and size spectra from ZooScan image analysis. (28th May 2022) - Cornils, Astrid; Thomisch, Karolin; Hase, Joanna; Hildebrandt, Nicole; Auel, Holger; Niehoff, Barbara
Abstract: The pelagic ecosystem of the Arctic Ocean is threatened by severe changes such as the reduction in sea‐ice coverage and increased inflow of warmer Atlantic water. The latter is already altering the zooplankton community, highlighting the need for monitoring studies. It is therefore essential to accelerate the taxonomic identification to speed up sample analysis, and to expand the analysis to biomass and size assessments, providing data for modeling efforts. Our case study in Fram Strait illustrates that image‐based analyses with the ZooScan provide abundance data and taxonomic resolutions that are comparable to microscopic analyses and are suitable for zooplankton monitoring purposes in the Arctic. We also show that image analysis allows to differentiate developmental stages of the key species Calanus spp. and Metridia longa and, thus, to study their population dynamics. Our results emphasize that older preserved samples can be successfully reanalyzed with ZooScan. To explore the applicability of image parameters for calculating total mesozooplankton and Calanus spp. biomasses, we used (1) conversion factors (CFs) translating wet mass to dry mass (DM), and (2) length–mass (LM) relationships. For Calanus spp., the calculated biomass values yielded similar results as direct DM measurements. Total mesozooplankton biomass ranged between 1.6 and 15 (LM) or 2.4 and 21 (CF) g DM m −2, respectively, which corresponds to previous studies in Fram Strait. Ultimately, a normalized biomass size spectra analysis provides 1 st insights into the mesozooplankton size structure at different depths, revealing steep slopes in the linear fit in communities influenced by Atlantic water inflow.